(untitled) (Bisanzio e l’Occidente, 2019)
Why did emperor Theodosius I (r. 379-395) devise to build a copy of the spiral Column of Trajan in his own Forum at Constantinople? The question undoubtedly involved the scholars’ attention for decades since the milestone works by Johannes Kollwitz and Giovanni Becatti had tried to provide the first answers. This article aims to assess the status quaestionis as well as the conclusions that have been reached so far. Mostly by drawing on recent contributions, it will provide a comprehensive overlook of the available literature and information, in order to understand either the urban context or the historical framework in which such a kind of extremely expensive and technically challenging endeavour apparently took place.